Features of the Pigment Complex of Winter Wheat Plants Depending on the Method of Fertilisation - Bilousova, Zoia; Білоусова, Зоя Володимирівна; Кенєва, Вікторія Анатоліївна; Keneva, Viktoria; Klipakova, Yuliia; Кліпакова, Юлія Олександрівна (My University, 2021)
EN: To maximise the yield of winter wheat, it is necessary to further optimise modern cultivation technologies to adapt them to changing environmental conditions. One of the aspects of plant adaptation to unfavourable abiotic factors is the active functioning of the photosynthetic apparatus, which depends on the number of nutrients applied. This paper investigates the effect of fertilisation on the state of the pigment complex of winter wheat plants in the Southern Steppe of Ukraine. Two varieties of winter wheat were selected for the study: Shestopalivka and Mason. The scheme of the experiment included the application of fertilisers during sowing (К0; К12) and foliar processing with various tank mixtures (urea; urea + magnesium sulphate; urea + magnesium sulphate + potassium monophosphate). The pigment content was determined by grinding fresh leaves of winter wheat with further addition of a solvent in the form of acetone. The pigments were measured usinga spectrophotometer. The results of the studies showed that before foliar fertilisation, the content of chlorophyll a and carotenoids was higher in the leaves of plants of the Shestopalivka variety. At the same time, the content of chlorophyll b was higher for Mason plants by 17%, which may be aтconsequence of the adaptation of plants of this variety to a lack of light. A decrease in the pigment content in the leaves of plants of all experimental variants caused by the active growth of the photosynthesising surface and a decrease in the total dry matter mass was observed on day 3 after the foliar fertilisation. There was no significant difference between varieties in the content of photosynthetic pigments during this period. On the 10th day after foliar spraying, an increase in the content of chlorophyll a and b was for both studiedvarieties,which may be the result of the adaptation of the photosynthetic apparatus of winter wheat plants to lighting conditions. Foliar fertilisation of winter wheat plants with a tank mixture of urea with magnesium sulphate and potassium monophosphate contributed to a further increase in the content of chlorophyll a by 12-23% and chlorophyll b by 5-37%, depending on the variety compared to the control. The results of the conducted research indicate the high efficiency of the complex application of nitrogen-phosphorus-potassium fertilisers for foliar spraying of winter wheat plants at the stage of BBCH 31 both on the background of pre-sowing potassium fertilizers and without it. /// UA: Для отримання максимальної врожайності озимої пшениці необхідна подальша оптимізація сучасних технологій вирощування з метою їх адаптації до мінливих умов навколишнього середовища. Одним із аспектів адаптації рослин до несприятливих абіотичних факторів є активне функціонування фотосинтетичного апарату, яке залежить від кількості внесених поживних речовин. У роботі досліджено вплив удобрення на стан пігментного комплексу рослин озимої пшениці в умовах Південного Степу України. Для дослідження було обрано два сорти озимої пшениці: Шестопалівка та Мейсон. Схема досліду включала внесення добрив під час сівби (К0 ; К12 ) та позакореневі обробки різними баковими сумішами (карбамід; карбамід + сульфат магнію; карбамід + сульфат магнію + монофосфат калію). Вміст пігментів визначали шляхом подрібнення свіжого листя озимої пшениці з подальшим додаванням розчинника у вигляді ацетону. Вміст пігментів вимірювали за допомогою спектрофотометра. Результати досліджень показали, що до позакореневого підживлення вміст хлорофілу а та каротиноїдів був вищим у листках рослин сорту Шестопалівка. Водночас вміст хлорофілу b був вищим у рослин сорту Мейсон на 17%, що може бути наслідком адаптації рослин цього сорту до нестачі світла. На 3-й день після позакореневого підживлення спостерігалося зниження вмісту пігментів у листках рослин усіх дослідних варіантів, що пов'язано з активним ростом фотосинтезуючої поверхні та зменшенням загальної маси сухої речовини. Суттєвої різниці між сортами за вмістом фотосинтетичних пігментів у цей період не спостерігалося. На 10 ту добу після позакореневого підживлення спостерігали збільшення вмісту хлорофілу a і b для обох досліджуваних сортів, що може бути наслідком адаптації фотосинтетичного апарату рослин пшениці озимої до умов освітлення. Позакореневе підживлення рослин пшениці озимої баковою сумішшю карбаміду з сульфатом магнію та монофосфатом калію сприяло подальшому підвищенню вмісту хлорофілу а на 12-23% та хлорофілу b на 5-37% залежно від сорту порівняно з контролем. Результати проведених досліджень свідчать про високу ефективність комплексного застосування азотно-фосфорно-калійних добрив для позакореневого обприскування рослин пшениці озимої у фазі ВВСН 31 як на фоні передпосівного внесення калійних добрив, так і без нього.
Особливості пігментного комплексу рослин пшениці озимої залежно від способу удобрення
Keywords: Triticum aestivum; foliar fertilisation; chlorophylls a and b; carotenoids; LHC; позакореневе підживлення; хлорофіли a і b; каротиноїди; ЛГК